Accept no substitutes! : the history of American advertising - Mierau, Christina B. (Minneapolis : Lerner, 2000)
Provides a social history of advertising in America, from its origins in the 1600s to the present, showing how it has influenced and been influenced by American culture.
Includes bibliographical references (p. 90-93) and index.
School Library Journal, September 2000
Books for the Teen Age (NYPL), May 2002
Booklist, July 2000
Bulletin (Center for Children's books), June 2000
Voice of Youth Advocates (V.O.Y.A.), August 2000
Keywords: Advertising -- History